Filter Surveillance Improves Performance. Issue 11 (1st November 2016) - Martin, Bard; Linder, Kevin
Abstract : Filter surveillance involves assessing a variety of water quality and operational parameters to evaluate filter performance as part of an ongoing, plant‐specific program.